Evaluating the shoreline and bottom terrain variations in the naval port of zone 5, Phu Quoc, Kien Giang by using multi - temporal remote sensing images - Luan, Nguyen The; Tien, Nguyen Ngoc; Tuan, Tran Anh; Nam, Le Dinh; Hung, Pham Duc; Tung, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2019)
In this study, the authors aim to study two major contents: (1) Evaluating the shoreline variation in the naval port of zone 5 (in the years of 1999, 2006, 2009 and 2016); (2) Evaluating the bottom terrain variation in the naval port of zone 5 (in the years of 2007 and 2010). Three main research methodologies were applied: (i) Band rationing method for the shoreline extraction; (ii) Shoreline change analysis method using GPS data; (iii) Digital elevation model integrated with bottom terrain analysis method. The most obvious change in shoreline is in the An Thoi port from Mui Den to Mui Ong Doi. In the shoreline from Mui Den to Mui Con Duong, a backward shoreline evolution (erosion) mainly occurred with an average width of about 40–50 m, while some other places had a forward shoreline evolution (accumulation), especially in Mui Con Duong with a width of 60 m. These sediment materials are sent to conductor and accumulation, making the bottom terrain raised. As on the sections AA’, BB’, CC’, DD’, we could see that the bottom terrain at the channel of naval port of zone 5 has the depth variation only from 2 m to 4 m. The accumulation rate is up to 1 m/year in this period.